REPEATED GIVING OF CASH WAQF: A CASE STUDY OF SABAH, MALAYSIA - Nurul Izzati Binti Justine; Mohamad Isa Abd Jalil (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines repeated waqf contributions in Sabah State, Malaysia. Religious obligation, benevolence, and familiarity with and trust in the waqf institution are the variables that are expected to have a positive relationship with the repeated behaviour of giving waqf cash. These antecedents are drawn from previous empirical studies. A total of 200 respondents who have repeatedly contributed to cash waqf shared their opinions through a survey form distributed by using the "convenience sampling" method. The collected data were then tested employing variance-based structural equation modelling and the partial least squares path modelling method using SmartPLS 3.3 software. The results of the analysis show that all the variables, namely religious adherence, benevolence, familiarity with the waqf institution, and trust in the waqf institution significantly influence the behaviour of repeated cash waqf contributions. The study findings could be used by future researchers as a point of reference. In practice, waqf institutions could also benefit from the findings by better understanding their donors' wishes and preferences.